The Consequences of Political Interference in Bureaucratic Decision Making : Evidence from Nigeria - Rogger, Daniel (World Bank, Washington, DC, 2018)
This paper investigates the consequences of granting politicians power over bureaucrats in the implementation of small-scale public infrastructure projects. While potentially bolstering the incentive for the executive to perform, increased legislative oversight may lead to distortions in the technocratic process for political gain. By assembling a nationally representative data set from Nigeria that tracks public projects from inception to audit, the paper finds evidence of a clear trade-off between political oversight and bureaucratic autonomy. Using an instrumental variables strategy in which early career choices of politicians are key determinants of legislative committee membership, the analysis finds that legislative influence increases the likelihood that a project is launched by 18 percent, but at the cost of reducing project quality by 15 percent and increasing the reported misuse of funds. The results highlight the fundamental tension between bureaucratic inaction and political corruption.